Study of arc behaviour during tungsten inert gas/metal inert gas hybrid welding of 5052A aluminium alloy - Rose Alifah Ellyana Roslan (2022)
MIG welding is an excellent welding process; however, it has arc stability limitations in the inert shielding gas. Thus, TIG/MIG hybrid welding is introduced to obtain a good quality MIG welding in the inert shielding gas. Although much research has been carried out on TIG/MIG hybrid welding process, only a few studies have used aluminium alloys and trailing TIG arc to study the behaviour of MIG arc. This study focuses on observing the influence of TIG arc on the arc behaviour, metal droplet transfer, weld profile, and porosity formation at weldments and the interaction between TIG and MIG arc during and after the welding process. To analyse the increase in the stability of the MIG arc through the TIG arc's hybridisation effect, a conventional MIG and TIG/MIG hybrid welding system with different TIG currents: 60 A, 100 A and 120 A was developed. The influence of TIG arc on the arc behaviour and metal droplet transfer was observed using a high-speed video camera. Weld profile and porosity formation was evaluated using a metallurgical microscope. A 2D numerical simulation was constructed to study the interaction between TIG and MIG arcs. The results showed that the arc interaction was generated between TIG and MIG arc and influenced the increase in the MIG arc's stability with the arc diameter and arc length increase after introducing TIG current as low as 60 A. As the arc length increased, the droplet frequency increased with the increase of the wire melting rate. The shallow penetration depth, excessive reinforcement height, small weld bead and weld toe angle were evaluated with increasing TIG current. Less porosity and a coarse pore were observed in 120 A of TIG current. These results suggest that the hybridisation effect of TIG and MIG arcs generates a strong arc interaction due to the MIG current distribution, improves the arc stability and welding performance, decreases the wettability of the molten metal and delays the solidification process.